Volatile Fatty Acids and Hydrogen as Substrates for Sulfate-Reducing Bacteria in Anaerobic Marine Sediment - Sørensen, Jan (1981)
The addition of 20 mM MoO(4)(2−) (molybdate) to a reduced marine sediment completely inhibited the SO(4)(2−) reduction activity by about 50 nmol g(−1) h(−1) (wet sediment). Acetate accumulated at a constant rate of about 25 nmol g(−1) h(−1) immediately after MoO(4)(2−) addition and gave a measure of the preceding utilization rate of acetate by the SO(4)(2−)-reducing bacteria. Similarly, propionate and butyrate (including isobutyrate) accumulated at constant rates of 3 to 7 and 2 to 4 nmol g(−1) h(−1), respectively. The rate of H(2) accumulation was variable, and a range of 0 to 16 nmol g(−1) h(−1) was recorded. An immediate increase of the methanogenic activity by 2 to 3 nmol g(−1) h(−1) was apparently due to a release of the competition for H(2) by the absence of SO(4)(2−) reduction. If propionate and butyrate were completely oxidized by the SO(4)(2−)-reducing bacteria, the stoichiometry of the reactions would indicate that H(2), acetate, propionate, and butyrate account for 5 to 10, 40 to 50, 10 to 20, and 10 to 20%, respectively, of the electron donors for the SO(4)(2−)-reducing bacteria. If the oxidations were incomplete, however, the contributions by propionate and butyrate would only be 5 to 10% each, and the acetate could account for as much as two-thirds of the SO(4)(2−) reduction. The presence of MoO(4)(2−) seemed not to affect the fermentative and methanogenic activities; an MoO(4)(2−) inhibition technique seems promising in the search for the natural substrates of SO(4)(2−) reduction in sediments.